How Entrepreneurship Orientation Influences the Performance of New Product Development in the SME in Bantul? - Diantoro, Aris Kusuno; Ikhsan, Foster; Kusmantini, Titik; Janah, Anisa Wardatul (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
The prosperity of a company depends heavily on the quality of its new product development. Small and medium-sized enterprises (SMEs) must regularly assess, update, and adapt their product line. It has been argued that entrepreneurial orientation is crucial to improving enterprise-level outcomes like company performance in today's competitive environment where product life cycles are getting shorter.  Objectives: This study aims to examine entrepreneurial orientation’s impact on new product development performance with business model innovation serving as a moderating variable. Methodology: The quantitative method is used in this study. The population under study consists of SMEs in Bantul Regency. This research employs a method of sampling known as purposive sampling with certain criteria. Partial Least Square (PLS) Structural Equation Modeling is utilized for analysis (SEM). Finding: This research shows that an entrepreneurial Orientation significantly affects the development of business model innovation. Product development performance is significantly influenced by the degree of innovation introduced into the business model and by the degree to which the entrepreneurial is oriented. Conclusion: Business model innovation is a great system for SMEs to bring their entrepreneurial spirit to innovation and also to improve the latest product development.